Liver cavernosal hemanginoma in childhood: a case report - Costa , Aloysio Ikaro Martins Coelho; Pereira, Erica Paulinne; Rodrigues, Fernando Fernandes; Nascimento , Lorrana Xavier do; Oliveira , Natalia Verzeletti; Cardoso, Tiago Magalhães (Brazilian Journal of Case Reports, 2021)
Cavernous hemangiomas are benign tumors that present a low risk of bleeding when considering their high prevalence. They are frequent in the liver, with a frequency of 5 to 20% in the population. They present an increased risk of rupture when larger than 10 cm and with central necrosis. It is a most common primary liver lesion, and its diagnosis can be made incidentally during nonspecific evaluation of abdominal complaints. It can be diagnosed in all age groups, most frequently in women around 30-50 years of age, and rarely in children over three years of age. About 90% of these lesions are diagnosed in the first six months of life.